Fab Lab-based learning: an environment to promote Women and Leadership in Engineering Education - Herrera, Pablo C. (2022)
The gender gap remains one of the outstanding problems in engineering education. However, there are global learning communities with more than a decade that show sustainable statistics for learning and leadership in STEM environments. This research analyzes the participation of women in the Fab Lab-based learning environment of the Fab Academy in the geography of IEEE Region 8 and the 28 countries that graduated 721 students between 2009 and 2021. We analyze the 31.21% of women graduated and the specificity of its scope in each sub region, from the context of the learning environment to those who management a Fab Lab. Demonstrating a line that takes up learned knowledge, orienting them to learning and leadership.